2019
DOI: 10.4102/sajr.v23i1.1760
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic kaposiform hemangioendothelioma complicated by Kasabach–Merritt phenomenon: A rare entity

Abstract: Primary pancreatic tumours are a rare and unusual entity in children. In this article, we present the case of an 8-month-old girl who presented with obstructive jaundice. The differential diagnosis based on imaging studies was that of a pancreatic vascular neoplasm; however, with the laboratory evidence of Kasabach–Merritt phenomenon (KMP), this prompted the diagnosis of pancreatic kaposiform hemangioendothelioma. A core biopsy of the pancreatic mass was taken at laparotomy and confirmed this diagnosis. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…[ 14 ] KHE is a rare tumor known to occur in infants or young children, with an incidence of approximately 0.07/100,000 children per year. [ 15 ] The pancreas is an extremely rare location for a KHE in a child, with only nine reported cases between 1973 and 2015. [ 14 , 16 ] KHE is commonly associated with the Kasabach–Merritt phenomenon, [ 17 ] whereby a retrospective study of 107 patients with KHE between 1991 and 2009 reported that the phenomenon developed in 71% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] KHE is a rare tumor known to occur in infants or young children, with an incidence of approximately 0.07/100,000 children per year. [ 15 ] The pancreas is an extremely rare location for a KHE in a child, with only nine reported cases between 1973 and 2015. [ 14 , 16 ] KHE is commonly associated with the Kasabach–Merritt phenomenon, [ 17 ] whereby a retrospective study of 107 patients with KHE between 1991 and 2009 reported that the phenomenon developed in 71% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with Kasabach-Merrit phenomenon, which is a combination of thrombocytopenia, hemolytic anemia, and consumptive coagulopathy (55). Histologically, KHE has an infiltrative growth pattern consisting of nodules and sheets of compact spindle cells with slitlike lumens, distinguishing these tumors from other pediatric vascular tumors (53,54). Immunohistochemical staining reveals positivity for lymphatic endothelial markers (D2-D40, ERG, CD31, and CD34) (53,55) and negativity for glucose transporter protein type 1, which is a marker of infantile hemangioma, another childhood vascular tumor (52,55).…”
Section: Kaposiform Hemangioendotheliomamentioning
confidence: 98%
“…Kaposiform hemangioendothelioma (KHE) is an aggressive infiltrative vascular tumor that commonly manifests during infancy or early childhood, and it most often affects the skin (51). KHE involving the pancreas is exceedingly rare, with fewer than 10 pediatric cases reported in the literature, all of which occurred in individuals within their first 3 years of life (52)(53)(54)(55).…”
Section: Kaposiform Hemangioendotheliomamentioning
confidence: 99%
See 2 more Smart Citations